PEDAGOGICAL SIGNIFICANCE OF THE CONTENT OF ECOLOGICAL EDUCATION IN HIGHER EDUCATION (Academia Science Repository, 2023)
Ecological education develops the student's interest in ecological problems and forms ideas about the image of the world. The attitude of the student to the natural and social environment is formed. The article highlights the importance of the pedagogical approach for the student's mastery of environmental education in higher education and gives practical suggestions.